ROS-scavenging hydrogel as protective carrier to regulate stem cells activity and promote osteointegration of 3D printed porous titanium prosthesis in osteoporosis - Ding, Wenbin; Zhou, Qirong; Lu, Yifeng; Wei, Qiang; Tang, Hao; Zhang, Donghua; Liu, Zhixiao; Wang, Guangchao; Wu, Dajiang (Frontiers in Bioengineering and Biotechnology, 2023)
Stem cell-based therapy has drawn attention as an alternative option for promoting prosthetic osteointegration in osteoporosis by virtue of its unique characteristics. However, estrogen deficiency is the main mechanism of postmenopausal osteoporosis. Estrogen, as an effective antioxidant, deficiency also results in the accumulation of reactive oxygen species (ROS) in the body, affecting the osteogenic differentiation of stem cells and the bone formation in osteoporosis. In this study, we prepared a ROS-scavenging hydrogel by crosslinking of epigallocatechin-3-gallate (EGCG), 3-acrylamido phenylboronic acid (APBA) and acrylamide. The engineered hydrogel can scavenge ROS efficiently, enabling it to be a cell carrier of bone marrow-derived mesenchymal stem cells (BMSCs) to protect delivered cells from ROS-mediated death and osteogenesis inhibition, favorably enhancing the tissue repair potential of stem cells. Further in vivo investigations seriously demonstrated that this ROS-scavenging hydrogel encapsulated with BMSCs can prominently promote osteointegration of 3D printed microporous titanium alloy prosthesis in osteoporosis, including scavenging accumulated ROS, inducing macrophages to polarize toward M2 phenotype, suppressing inflammatory cytokines expression, and improving osteogenesis related markers (e.g., ALP, Runx-2, COL-1, BSP, OCN, and OPN). This work provides a novel strategy for conquering the challenge of transplanted stem cells cannot fully function in the impaired microenvironment, and enhancing prosthetic osteointegration in osteoporosis.